Revisiting the Ullman's Radical Chemistry for Phthalocyanine Derivatives - Fidan, Ismail; Luneau, Dominique; Ahsen, Vefa; Hirel, Catherine (Wiley-V C H Verlag Gmbh, 2018)
Phthalocyanine derivatives do not cease to gain attention due to their numerous properties and applications (e.g., sensor, PDT). This makes them a unique scaffold for the design of new material. In this context, we were interested to develop the synthesis of an imino nitroxide-substituted phthalocyanine by Ullman's procedure; a challenge due to the intrinsic low solubility of most phthalocyanine derivative in much solvents. To overcome this solubility problem, we designed a phthalocyanine with bulky neopentyl substituents in peripheral positions as counterpart to the imino nitroxide moieties. The imino nitroxide-substituted phthalocyanine was obtained by condensation of a monoformyl-substituted phthalocyanine with 2,3-bis(hydroxylamino)-2,3-dimethylbutane in refluxing THF-MeOH (2:1) mixture in the presence of p-toluenesulfonic acid monohydrate, follow by oxidation with PbO2. Characterization was performed by electrochemistry, UV/Vis and EPR spectroscopy in solution as well as SQUID in solid state.
Keywords: dehydration; formyl-substituted phthalocyanine; imino nitroxide; radical; Ullman's synthesis